Pengaruh Media Pembelajaran Canva Terhadap Minat Belajar Siswa Pada Mata Pelajaran Desain - Wildan Fathu Romdhon; Sofhian Fazrin N (CV.ITTC INDONESIA, 2025)
This study aims to analyze the effect of using Canva as a learning medium on students’ learning interest in Design subjects at SMK Negeri 3 Kuningan. The research employed a quantitative approach with a one-group pretest-posttest design involving 30 tenth-grade students of the Visual Communication Design program. A learning interest questionnaire was administered before and after the treatment. The results showed that the average pretest score was 32.03, which increased to 43.47 in the posttest. The Wilcoxon Signed Rank Test yielded Z = -4.579 with a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest. The effect size calculation produced r = 0.85, which is categorized as very large. These findings confirm that Canva has a strong effect in enhancing students’ learning interest and can serve as an effective, interactive, and engaging learning medium.